2011
DOI: 10.1258/ebm.2010.010308
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide inhibits macrophage-derived foam cell formation

Abstract: Recent evidence indicates that hydrogen sulfide (H(2)S) exerts an antiatherogenic effect, but the mechanism is unclear. Formation of macrophage-derived foam cells is a crucial event in the development of atherosclerosis. Thus, we explore the effect of H(2)S on the formation of macrophage-derived foam cells. Incubation of monocyte-derived macrophages with oxidized LDL (oxLDL) alone caused significant increases both in intracellular lipids revealed by Oil-red O staining and in intracellular total cholesterol (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 24 publications
2
60
0
4
Order By: Relevance
“…Previous studies have demonstrated that H 2 S can inhibit macrophage-derived foam cell formation (16,(25)(26). Our research group confirmed that H 2 S generation in vessels was decreased in apoE Ϫ/Ϫ mice and that it was an important factor in the formation and development of atherosclerosis (16).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have demonstrated that H 2 S can inhibit macrophage-derived foam cell formation (16,(25)(26). Our research group confirmed that H 2 S generation in vessels was decreased in apoE Ϫ/Ϫ mice and that it was an important factor in the formation and development of atherosclerosis (16).…”
Section: Discussionsupporting
confidence: 83%
“…For instance, H 2 S plays an antiatherogenic role by suppressing the formation of human macrophage foam cells. H 2 S inhibits the formation of macrophage-derived foam cells, which is a crucial event in the development of atherosclerosis, by downregulating CD36, SR-A, and ACAT-1 expression and inhibiting oxidized low-density lipoprotein (oxLDL) binding and uptake of macrophages (66,67). In addition to its important role in preventing atherosclerosis, H 2 S has also direct benefits for coronary heart disease (CHD) patients.…”
Section: H 2 S: a Novel Therapeutic Agent In Age-associated Diseases?mentioning
confidence: 99%
“…Other therapies target IFN-γ via alternative signaling pathways, for example, ACS14 (a hydrogen sulphide releasing aspirin) is capable of attenuating the expression of IFN-γ-stimulated CX3 chemokine receptor 1 (CX3CR1) via a peroxisome proliferator-activated receptor-γ-dependent mechanism [48] . Hydrogen sulphide has previously been shown to exert anti-atherogenic effects and its use in ACS14 has been shown to reduce atherosclerosis development in ApoE mice models [48,49] . IFN-γ neutralization involves the use of a soluble IFN-γR (sIFN-γR) which acts as decoy receptor to prevent the activation of IFN-γR and in turn the phosphorylation of STAT1 in the JAK-STAT pathway, in effect "neutralizing" the IFN-γ.…”
Section: Resultsmentioning
confidence: 99%